A system dynamics model for assessing the impacts of design errors in construction projects - Han, Sangwon; Love, Peter; Peña-Mora, Feniosky (Pergamon, 2013)
Design errors leading to rework and/or design changes are considered to be the primary contributor to schedule delays and cost overruns in design and construction projects. While design errors are deemed prevalent, most design and construction firms do not measure the number of errors they create, thereby having limited knowledge regarding their mechanism to undermine project performance. To address this, a system dynamics model has been developed to capture the dynamics of design errors and systematically assess their negative impacts. This paper reports on the development of the model, and its application to a university building project. The results indicate that design errors can significantly delay project schedule in spite of continuous schedule recovery actions taken by construction managers. The case study also shows that schedule pressure can propagate the negative impact of design errors to numerous construction activities, including those that are not directly associated with the errors. Finally, the case study confirms that the developed model can more rigorously assess the negative impact of design errors, which is often underestimated by practitioners. Based on these results, it is concluded that the developed model can assist project managers in better understanding the dynamics of design errors and recovering delayed schedule, particularly under schedule pressure.